2016
DOI: 10.1016/j.addbeh.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and cannabis use among college students: Substitutes or complements?

Abstract: Aims Economists debate whether changes in availability of alcohol or cannabis are positively or negatively related to changes in use of the other substance. Implicit in these arguments are two competing, individual-level hypotheses—that people use alcohol and cannabis either as complements or substitutes for one another. This is the first study to test these hypotheses using micro-longitudinal data on individuals’ alcohol and cannabis use on a given evening. Methods United States college students who use alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 43 publications
4
44
3
1
Order By: Relevance
“…Moreover, given that a recent study found heterogeneity in types of marijuana users (Pearson et al, in press-b), future research is needed to examine how different types of marijuana users across various states celebrate 4/20, which would supply unique information as to who might be at risk for excessive consumption and/or consequences on 4/20. Additionally, given that alcohol use and marijuana use are complementary among college students (O'Hara et al, 2016), future research is needed to examine how polysubstance use may place students at elevated risks for negative consequences on 4/20.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Moreover, given that a recent study found heterogeneity in types of marijuana users (Pearson et al, in press-b), future research is needed to examine how different types of marijuana users across various states celebrate 4/20, which would supply unique information as to who might be at risk for excessive consumption and/or consequences on 4/20. Additionally, given that alcohol use and marijuana use are complementary among college students (O'Hara et al, 2016), future research is needed to examine how polysubstance use may place students at elevated risks for negative consequences on 4/20.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Yet another possible explanation for the inconsistency regarding whether alcohol and cannabis act as substitutes or complements was presented by O'Hara et al . . Here, the authors concluded that complementary use was common among US college students, whereas substitution was more likely among those using alcohol and/or cannabis to cope with stress .…”
Section: Discussionmentioning
confidence: 83%
“…. Here, the authors concluded that complementary use was common among US college students, whereas substitution was more likely among those using alcohol and/or cannabis to cope with stress . This suggests that the question of substitution or complementarity is not only a matter of settings but can also vary between subgroups in a given setting, depending on the motives for using different substances.…”
Section: Discussionmentioning
confidence: 86%
“…Future research on retention outcomes should measure marijuana use that is independent of whether or not a clinic or study visit is attended. This could be done using techniques such as ecologic momentary assessment or daily diaries (4851). Finally, consistent with other retention studies, cancelled visits were not considered missed visits and were ignored in the analysis.…”
Section: Discussionmentioning
confidence: 99%